Inovasi Evaluasi Kurikulum dalam Mewujudkan Madrasah Unggulan di MA Darul Ulum Peterongan Jombang - Agus Moh. Sholahuddin; Ahmad Muthi’Uddin; M. Ainun Najib; Siti Nur Afifah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Madrasah Aliyah Darul Ulum Jombang has implemented curriculum evaluation innovations to measure success and continuously improve the quality of education as a leading madrasah. This research focuses on curriculum evaluation innovations, supporting and inhibiting factors, and their impact on realizing a leading madrasah. This study uses a qualitative phenomenological approach with interview, observation, and documentation methods. Data analysis was conducted through case studies, data collection, and drawing conclusions. The purpose of this research is to contribute to the study and development of curriculum management theory in Islamic educational institutions. The results show that curriculum evaluation innovations are not only limited to context, process, and product, but also encompass the results. This is done by the head of the madrasah by many means, including consultation .2) The supporting factors are the full support from the Leadership of the Darul Ulum Islamic Boarding School by reviewing and providing direction regarding curriculum evaluation, competent human resources in the curriculum field, adequate facilities. Meanwhile, the inhibiting factor is that there are no limits in evaluation, evaluation is carried out according to the development of the times and the conditions of the applied curriculum. 3) The impact of curriculum evaluation innovation is to create a positive learning space, change the education system for the better, and produce competent students.